How Do Curbside Feedback Tactics Impact Households’ Recycling Performance? Evidence From Community Programs - McKie, Erin C; Chandrasekaran, Aravind; Venkataraman, Sriram (Production and Operations Management, 2024)
Much of the responsibility for advancing the circular economy has been directed towards firms, yet many reuse opportunities can only be achieved through environmentally compliant, household-level recycling behaviors. In response, policymakers and recycling organizations are using a range of feedback mechanisms to promote household recycling that meets local quality standards. However, the effectiveness of these tactics remains unclear, and stakeholders are divided on the appropriateness of their use. In this research, we examine the role of two popular feedback mechanisms—information-only and information-plus-penalty—in correcting households’ curbside recycling behaviors. With information-only feedback, households are provided with best practices for recycling and are not penalized for their errors. With information-plus-penalty feedback, households also receive information, but temporarily forfeit their recycling services. While previous studies have explored the use of information and penalties as feedback mechanisms to guide behavioral changes, there is mixed evidence of their effectiveness, particularly in the recycling context. We address this research gap by analyzing unique data collected from a 2019 curbside auditing effort that occurred in a large, Mid-Western city. Our analysis leverages econometric methods, and recycling feedback and performance data from 25,359 audits across 11,899 households and 15 recycling routes. We find that information-only feedback mechanisms, while preferred by some stakeholders, are not associated with improvements in recycling quality (measured using household contamination rates). By contrast, our results indicate that punitive mechanisms (i.e., information-plus-penalty) involving cart refusals are associated with significant reductions in contamination rates: that is, households that receive punitive feedback reduce their contamination rate severity by 59%, and are 75% less likely to commit a violation in the future. More importantly, we do not find evidence that punitive feedback mechanisms generally discourage households’ participation in recycling programs (measured using future set out rates). Our study informs sustainable operations management literature by investigating how curbside feedback mechanisms, with differing levels of severity, influence critical dimensions of households’ recycling performance (i.e., recycling quality and participation). We also inform policymakers on how curbside feedback mechanisms can be more effectively leveraged to enhance opportunities for material reuse.